A Randomized Controlled Trial of a Non-pharmacological Intervention for Cancer-Related Dyspnea - Yates, Patsy; Hardy, Janet; Clavarino, Alexandra; Fong, Kwun M.; Mitchell, Geoffrey; Skerman, Helen; Brunelli, Vanessa; Zhao, Isabella (Frontiers in Oncology, 2020)
Objectives To evaluate the efficacy of a brief tailored non-pharmacological intervention comprising breathing retraining and psychosocial support for managing dyspnea in cancer patients. Design Multicenter, single blinded, parallel group, randomized controlled trial. Setting Four major public hospitals, Brisbane, Australia. Participants 144 cancer patients, including 81 who received an 8-week tailored intervention and 63 who received standard care. Inclusion criteria: diagnosis of small or non-small cell lung cancer, mesothelioma or lung metastases; completed first line therapy for the disease; average dyspnea rating >2 on (0-10) rating scale in past week; anticipated life expectancy ≥3 months. Outcomes The primary outcome measure was change in ‘worst’ dyspnea at 8 weeks compared to baseline. Secondary outcomes were change in: dyspnea ‘at best’ and ‘on average’; distress; perceived control over dyspnea; functional status, psychological distress; and use of non-pharmacological interventions to manage dyspnea at 8 weeks relative to baseline. Results The mean age of participants was 67.9 (SD=9.6) years. Compared to the control group, the intervention group demonstrated a statistically significant: (i) improvement in average dyspnea from T1(M=4.5, SE=.22) to T3 (M=3.6, SE=.24) versus (M=3.8, SE=.24) to (M=4.1, SE=.26); (ii) greater control over dyspnea from T1 (M=5.7, SE=.28) to T3 (M=7.5, SE=.31) versus (M=6.8, SE=.32) to (M=6.6, SE=.33); and (iii) greater reduction in anxiety from T1 (M=5.4, SE=.43) to T3 (M=4.5, SE=.45) versus (M=4.2, SE=.49) to (M=4.6, SE=.50). This study found no intervention effect for best and worst dyspnea, distress from breathlessness, functional status, and depression over time. Conclusions This study demonstrates efficacy of tailored non-pharmacological interventions in improving dyspnea on average, control over dyspnea, and anxiety for cancer patients.